Stosunek młodzieży szkół białostockich do wybranych norm moralnych - Zemło, Mariusz (Zeszyty Naukowe Katolickiego Uniwersytetu Lubelskiego Jana Pawła II, 2023)
This text presents opinions of adolescents studying in Bialystok schools concerning selected moral behaviours. Among these behaviors were sexual life before marriage, use of contraception, marital infidelity, divorce, termination of pregnancy and homosexuality. In the material presented here, the following independent variables were taken into account: gender, age, type of school, participation in religious practices. In order to keep the results within a background that gives more insight into them, they were confronted with the data obtained by other researchers in different environments, as well as to the data obtained from studies that were conducted in Bialystok in 2005, 2011, 2015, 2019.